Reference values of urinary metabolites of organophosphate in healthy Iranian adults - Rosa Haghshenas; Zahra Soleimani; Yosef Farzi; Amirmohammad Khalaji; Amir Hossein Behnoush; Ali Taherkhani; Ashkan Pourabhari Langroudi; Shahedeh Seyfi; Nasim Hadian; Mohammadhassan Momayyezi; Samaneh Mozafari; Samaneh Abolli; et al. (PLoS ONE, 2025)
Organophosphorus pesticides are widely used in agriculture in Iran; we evaluated exposure to these pesticides among Iranian adults. Pesticide-specific urinary metabolites were used as biomarkers for exposure to various pesticides, including organophosphorus insecticides. The aim of the study was to estimate reference values (RV95) and their relationships with the measured factors. We used the 95th percentile as the basis for deriving these reference values. The analysis included descriptive statistics and multiple linear regression, conducted using Python software. We measured metabolites for Chlorpyrifos (TCP: 2-isopropyl-4-methyl-6-hydroxypyrimidine), Diazinon (IMPY: 2-isopropyl-4-methyl-6-hydroxypyrimidine), and Malathion (Malathion dicarboxylic acid) in 490 healthy Iranian adults. Additionally, we recorded age, gender, wealth index, and body composition parameters including body fat, muscle mass, visceral fat, and BMI. Fasting urine sampling, along with body composition and demographic measurements, were conducted. Urine samples were subsequently analyzed. The Chlorpyrifos, Diazinon, and Malathion Reference Value (RV95) levels ranged from ND-24.9 µg/L (RV95: 2.8 µg/L, 2.9 µg/gcrt), ND-64.36 µg/L (RV95: 8.6 µg/L, 9.3 µg/gcrt), and ND-47.69 µg/L (RV95: 9.8 µg/L, 8.2 µg/gcrt), respectively. Diazinon (IMPY) and Malathion (Malathion dicarboxylic acid) showed no significant relationship between their urinary levels and demographic features. However, visceral fat percentage had a significant inverse correlation with urinary levels of Chlorpyrifos (TCP) (P = 0.038). Other factors such as age, sex, visceral fat, BMI, and wealth index showed no significant relationship with urinary levels (P > 0.05). Non-zero levels were found in 98.8% of adults’ urine samples for this metabolite. The reference value of this pesticide metabolite in urine could be helpful for policymakers in assessing the level of exposure among Iranians.